International Aid Withdrawal as a Systemic Livelihood Shock: Socioeconomic Consequences in Rural Bangladesh - Shifat Anwar Tumpa; Ashraful Siddique; Mohammad Anwarul Islam Pathan; Apu Debnath; MD Sayeed Mostafa; Md. Atikul Islam; Rakib Hossain (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2026)
Abstract International aid has supported rural livelihoods, essential services, and climate resilience in Bangladesh. However, recent donor withdrawal has disrupted development interventions, while its community-level consequences remain insufficiently examined, particularly in climate-exposed rural areas. This study investigates how aid cuts affect livelihoods, service access, social vulnerability, and climate-response capacity across four districts. Using a qualitative design, data were collected in Kurigram, Sunamganj, Khulna, and Rajshahi through 12 focus group discussions and eight key informant interviews with farmers, women, youth, former beneficiaries, local officials, NGO personnel, community leaders, and former project staff. The data were transcribed, translated where necessary, and analysed thematically using Braun and Clarke’s six-phase approach, with triangulation and participant validation. The findings show that aid withdrawal functioned as a systemic livelihood shock, disrupting agricultural production, income, healthcare, education, nutrition, women’s economic activities, and disaster preparedness. These effects were most severe where local institutions and markets could not replace withdrawn support. The study contributes a community-level framework for understanding donor exit. It implies that aid transitions should be gradual, institutionally prepared, and designed to protect essential services and adaptive capacity. The study concludes that poorly managed withdrawal can deepen existing rural and climate-related vulnerabilities.